Examining Entrepreneurial Intention among Business School Students in Indonesia - Handayani, Nurina Putri; Yuniawan, Ahyar; Devyanadine, Devyanadine (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Encouraging students to become entrepreneurs can help alleviate the problem of the increasing number of unemployed in Indonesia due to the limited number of jobs, especially during the Covid-19 pandemic. The main objective of this research is to find out what factors encourage students to become entrepreneurs. This research analyzes the effect of personal attitude, perceived behavioral control, and subjective norms on entrepreneurial intentions. An online survey was conducted to collect primary research data.Â The total number of respondents of this study was 251, who were students majoring in Management and Business in Banten Province, Indonesia. Models and hypotheses are tested using Structural Equation Modeling (SEM). SEM was considered to be a proper means for this analysis because the interpretive structural model involves multiple-path linkages between variables. The results of this study indicate that personal attitude and perceived behavior have a positive significant influence on entrepreneurial intention, while a relationship between subjective norm and entrepreneurial, was found to be a non-significant